2009
DOI: 10.3928/01477447-20090915-54
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PCL on Flexion-Extension Gaps and Femoral Component Decision in TKA

Abstract: This study was done to evaluate the change of medial-lateral gap in flexion and extension after posterior cruciate ligament (PCL) release in severely deformed knees and to determine how PCL release affects bone resection, rotation, and size of the femoral component and polyethylene thickness in converting to a PCL-sacrificed design. Thirty primary osteoarthritis patients with severe varus deformity or flexion contracture were enrolled. After releasing the PCL, the medial gap in extension increased by 1.2 mm, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…These results are generally in line with the majority of existing studies [9,[16][17][18][19][20]. In this context, we investigated high flexion grades and found that the biggest joint-gap increase was between 110°and 140°.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results are generally in line with the majority of existing studies [9,[16][17][18][19][20]. In this context, we investigated high flexion grades and found that the biggest joint-gap increase was between 110°and 140°.…”
Section: Discussionsupporting
confidence: 91%
“…If the gap-balanced procedure is used, PCL release leads to a constant reduction of the femoral component's external rotation. Similarly, Park et al measured a reduced external rotation of the femoral component of 1.6°after PCL resection [20].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…By searching the PubMed database with the strategy of 'TKA PCL gap flexion extension', we finally located eight articles [5][6][7][8][9][10][11][12] concerning the differences in the gap balance after PCL resection after viewing the titles and the reference lists of related articles (Table 2). Among these studies, the results of Kadoya et al 7 and Park et al 10 suggested that the distance of medial gap increased more compared with the lateral gap, in other words, decreasing the degrees of the varus deformity, which are consistent to our work with high distract force (20 and 30 in-lbf). Conversely, Baldini et al's 8 research agrees with the present study that under low distraction force the degree of varus deformity remains the same.…”
Section: Discussionmentioning
confidence: 99%